(untitled) (Polish Yearbook of International Law, 2021)
Hardly any sector has been hit as hard by the COVID-19 pandemic as the air transport industry. As lockdown measures are lifted, a recovery phase begins that will shape the global economic landscape for the years to come. In this context this paper raises the question of whether the pre-existing EU instruments for subsidizing air operations – Startup aid and the Public Service Obligation – none of which was designed with economic recovery in mind – can be adapted to the new circumstances after the current ad hoc measures under the Temporary Framework have dried up. The hypothesis which is taken as a starting point is that the existing state aid toolbox has built-in deficiencies which are hampering recovery efforts. This paper therefore attempts to determine whether alternatives can be sought within the confines of the EU state aid law, and if so what such alternatives might be.